LABORS POSITIONS LABOR MANAGEMENT COMMITTEE RESOURCES (Tufts Archival Research Center, 2007)
Report listing organized labor's position on tobacco-related issues and resources of the Labor Management Committee. States position of labor regarding employment discrimination, excise taxes, indoor air quality, and workplace smoking policies.